Analysis of imaging risk factors for prognosis in children with spinal cord injury without radiologic abnormalities - Junyi Hu; Cui Wang (Scientific Reports)
Abstract This study aimed to identify imaging risk factors for spinal cord injury without radiologic abnormalities (SCIWORA) in children. We retrospectively analyzed the medical records and magnetic resonance imaging (MRI) findings of children with SCIWORA admitted to our hospital between January 1, 2012, and September 30, 2022. Univariate and binary logistic regression analyses were used to evaluate the prognostic impact of various factors including MRI type, maximum cross-sectional area of spinal cord injury, injury length, injury signal intensity ratio. The American Spinal Injury Association (ASIA) impairment scale (AIS) was used to assess neurological improvement of spinal cord injury. A total of 39 patients met the inclusion criteria, comprising three males and 36 females aged 6.38 ± 1.7 years. The injuries were predominantly dance-related (25 patients), followed by car accidents (4 patients), and falls/sprains (10 patients). Seventeen patients showed improvement in the AIS grade, while 22 did not. Binary logistic regression analysis revealed that the maximum cross-sectional area and length of the damaged segment were significant prognostic factors. Receiver operating characteristic curve analysis demonstrated an area under the curve (AUC) of 0.91, with a maximum cutoff value, sensitivity, and specificity of 0.12, 81.80%, and 88.20%, respectively, for the maximum damage cross-sectional area. For the damaged segment length, the AUC, maximum cutoff value, sensitivity, and specificity were 0.78, 6.50, 50%, and 41%, respectively. Whole-spine MRI plays a crucial role in the diagnosis and prognosis of pediatric patients with SCIWORA. The cross-sectional area and length of spinal cord injury are risk factors for poor prognosis. Level of evidence: IV